Updates in Volcanology - Transdisciplinary Nature of Volcano Science - Károly Németh (IntechOpen, 2021)
Updates in Volcanology - Transdisciplinary Nature of Volcano Science is a true reflection of the recent advancement of volcano science to a geosystem science based on a strong source-to-surface or process-to-consequences nature, all centered around the transdisciplinary nature of volcanology. The book contains a balanced set of chapters dealing with traditional approaches within volcanology from petrogenetic aspects of magmatic systems to volcano models. The book also provides a comprehensive set of outputs along volcanic geoheritage.